Membrane Interactions of Oligomeric Alpha-Synuclein: Potential Role in Parkinson's Disease - D. van Rooijen, Bart; M.A.E. Claessens, Mireille; Subramaniam, Vinod (Current Protein and Peptide Science, 2010)
α-Synuclein is a small neuronal protein that has been implicated to play an important role in Parkinson's disease. Genetic mutations and multiplications in the α-synuclein gene can cause familial forms of the disease. In aggregated fibrillar form, α-synuclein is the main component of Lewy bodies, the intraneuronal inclusion bodies characteristic of Parkinson's disease. The loss of functional dopaminergic neurons in Parkinson's disease may be caused by a gain in toxic function of the protein. Elucidating if this gain of toxic function is related to the aggregation of α-synuclein may be vital in understanding Parkinson's disease. Although there are many ideas on how α-synuclein could be involved in the disease, this review will focus on the amyloid pore hypothesis. This hypothesis assumes that aggregation intermediates or oligomers are more likely to be toxic than monomeric or fibrillar forms of the protein. Oligomeric species are thought to exercise their toxicity through permeabilization of cellular membranes. Membrane pore formation by an oligomeric intermediate might play a role in other neurodegenerative disorders in which protein aggregation and amyloid formation play a role, such as Alzheimer's disease. We will discuss the role of this hypothesis in Parkinson's disease.
Keywords: disruption